Monogenic Causes of Apparently Idiopathic Perinatal Intracranial Hemorrhage. Issue 4 (16th February 2021) - Hausman‐Kedem, Moran; Malinger, Gustavo; Modai, Shira; Kushner, Steven A.; Shiran, Shelly I.; Ben‐Sira, Liat; Roth, Jonathan; Constantini, Shlomi; Fattal‐Valevski, Aviva; Ben‐Shachar, Shay
Abstract : Objective: Perinatal intracranial hemorrhage (pICH) is a rare event that occurs during the fetal/neonatal period with potentially devastating neurological outcome. However, the etiology of pICH is frequently hard to depict. We investigated the role of rare genetic variations in unexplained cases of pICH. Methods: We performed whole‐exome sequencing (WES) in fetuses and term neonates with otherwise unexplained pICH and their parents. Variant causality was determined according to the American College of Medical Genetics and Genomics (ACMG) criteria, consistency between suggested genes and phenotypes, and mode of inheritance. Results: Twenty‐six probands (25 families) were included in the study (9 with a prenatal diagnosis and 17 with a postnatal diagnosis). Intraventricular hemorrhage (IVH) was the most common type of hemorrhage (n = 16, 62%), followed by subpial (n = 4, 15%), subdural (n = 4, 15%), and parenchymal (n = 2, 8%) hemorrhage. Causative/likely causative variants were found in 4 subjects from 3 of the 25 families (12%) involving genes related to the brain microenvironment ( COL4A1, COL4A2, and TREX‐1 ). Additionally, potentially causative variants were detected in genes related to coagulation ( GP1BA, F11, Von Willebrand factor [ VWF ], FGA, and F7 ; n = 4, 16%). A potential candidate gene for phenotypic expansion related to microtubular function ( DNAH5 ) was identified in 1 case (4%). Fifty‐five percent of the variants were inherited from an asymptomatic parent. Overall, these findings showed a monogenic cause for pICH in 12% to 32% of the families. Interpretation: Our findings reveal a clinically significant diagnostic yield of WES in apparently idiopathic pICH and support the use of WES in the evaluation of these cases. ANN NEUROL 2021;89:813–822